Influence of different maceration time and temperatures on total phenols, colour and sensory properties of Cabernet Sauvignon wines - Şener, Hasan (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2013)
Maceration and fermentation time and temperatures are important factors affecting wine quality. In this study different maceration times (3 and 6 days) and temperatures (15  and 25 ) during production of red wine (Vitis vinifera L. Cabernet Sauvignon) were investigated. In all wines standard wine chemical parameters and some specific parameters as total phenols, tartaric esters, total flavonols and colour parameters (CD, CI, T, dA%, %Y, %R, %B, CIELAB values) were determined. Sensory evaluation was performed by descriptive sensory analysis. The results demonstrated not only the importance of skin contact time and temperature during maceration but also the effects of transition temperatures (different maceration and fermentation temperatures) on wine quality as a whole. The results of sensory descriptive analyses revealed that the temperature significantly affected the aroma and flavour attributes of wines. The highest scores for 'cassis', 'clove', 'fresh fruity' and 'rose' characters were obtained in wines produced at low temperature (15 ) of maceration (6 days) and fermentation